RECENT OSTRACODS (FAMILY TRACHYLEBERIDIDAE) FROM THE SOUTHERN BRAZILIAN CONTINENTAL SHELF (Ameghiniana, 2012)
The present study is a further contribution to the systematic knowledge of the ostracods from the southern Brazilian continental shelf. Twelve species of Trachyleberididae are recorded, including the following six new taxa: Cativella ornelasae sp. nov., C. sudbrasilienis sp. nov. sp., Henryhowella inflata sp. nov., Henryhowella verrucosa sp. nov., Ambocythere venusta sp. nov. and Basslerites costata sp. nov. The other six species have been recorded in previous studies, either in shallow or bathyal depths in both Brazilian waters and adjacent areas. Most species recorded herein are distributed in the neritic zone, except three, i.e., Trachyleberis aorata, Ambocythere venusta sp. nov. and C. sudbrasilienis sp. nov. The first two species are eurybathic, while C. sudbrasilienis sp. nov. is restricted to the inner shelf.Resumen. OSTRÁCODOS (FAMILIA TRACHYLEBERIDIDAE) RECIENTES DE LA PLATAFORMA CONTINENTAL DEL SUR DE BRASIL. El presente estudio es una contribución más al conocimiento de la sistemática de ostrácodos de la plataforma continental del sur de Brasil. Se registraron doce especies de Trachyleberididae, siendo seis de ellas nuevas: Cativella ornelasae sp. nov., C. sudbrasilienis sp. nov., Henryhowella inflata sp. nov., Henryhowella verrucosa sp. nov., Ambocythere venusta sp. nov. y Basslerites costata sp. nov. Las demás especies ya habían sido registradas en otros estudios en aguas someras o batiales, no solo en el margen continental brasileño sino también en áreas adyacentes. La mayoría de las especies registradas se distribuye a lo largo de la zona nerítica, a excepción de tres: Trachyleberis aorata, Ambocythere venusta sp. nov. y C. sudbrasilienis sp. nov. Las dos primeras parecen ser euribáticas, mientras C. sudbrasilienis sp. nov. se limita a la plataforma interna.